2018
DOI: 10.1111/clr.13139
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength of zirconia implant abutments on narrow diameter implants with internal and external implant abutment connections: A study on the titanium resin base concept

Abstract: For narrow diameter abutments, the fracture strength of 2-piece internal connected zirconia abutments fixed on titanium resin bases was similar to those obtained for 1-piece titanium abutments. Narrow diameter zirconia abutments with internal connection exhibited higher fracture strength than zirconia abutments with an external connection. Titanium abutments with an internal connection were significantly stronger than identical zirconia abutments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 19 publications
3
63
1
2
Order By: Relevance
“…No screw loosening, or veneer complication was found. On the other hand, the use of rigid frameworks fabricated by metal or zirconia could lead to plastic deformation of the implant shoulder [73,74]. These results are in consistency with the in vitro study of Kaleli et al reporting higher stress values of zirconia customized abutments on implant components, crown and cortical bone, compared to PEEK customized abutments [9].…”
Section: Implant-supported Fixed Dental Prostheses (Ifdps)supporting
confidence: 84%
“…No screw loosening, or veneer complication was found. On the other hand, the use of rigid frameworks fabricated by metal or zirconia could lead to plastic deformation of the implant shoulder [73,74]. These results are in consistency with the in vitro study of Kaleli et al reporting higher stress values of zirconia customized abutments on implant components, crown and cortical bone, compared to PEEK customized abutments [9].…”
Section: Implant-supported Fixed Dental Prostheses (Ifdps)supporting
confidence: 84%
“…The use of mesostructure to build the hybrid abutment to replace the conventional titanium abutments has already been reported [21,26,45]. Up to date, in vitro [26,47,48] and in vivo [49] studies and case reports [50,51] reported the use of lithium disilicate or polycrystalline ceramics to manufacture the mesostructure. Meanwhile, one case report [15] and in silico investigations [22][23][24][25] showed the possibility to manufacture the hybrid abutment using PIC material cemented on a Tibase, as performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…More recent types of ceramic abutments include metal hybrid secondary components to increase the stability at the level of the connection might be the preferred option in future. Internally connected zirconia abutments supported by titanium base abutments exhibited significantly higher strength in vitro studies than one‐piece zirconia abutments, in addition, the bending moments of these titanium base‐supported zirconia abutments were similar to the ones of metal abutments (Sailer et al., ). Other studies also demonstrated more favorable fracture strength values of ceramic abutment supported by hybrid abutments, as compared to one‐piece ceramic abutments (Alsahhafa, Spies, Vachc & Kohal, ; Butz, Heydecke, Okutan & Strub, ; Chun et al., ; Elsayed, Wille, Al‐Akhali & Kern, ; Sailer, Sailer et al., ; Stimmelmayr et al., ; Yilmaz, Salaita, Seidt, McGlumphy & Clelland, ).…”
Section: Discussionmentioning
confidence: 99%